A Delphi study on health literacy competencies for health professionals - Anna-Sophia Beese; Rebecca Jaks; Elena Alder; Saskia Maria De Gani (BMC Medical Education)
Abstract Background Health professionals play a key role in promoting health literacy, as they continue to be one of the main points of contact and most trusted source of information for healthcare users on questions and concerns regarding health and disease. To adequately support individuals in dealing with health information and services and to strengthen health literacy, health professionals need a corresponding set of knowledge, skills, and attitudes, hence they need a wide range of health literacy competencies. Despite their crucial role in guiding and supporting patients and their relatives in terms of health-related information and services, in-depth studies on health literacy competencies of health professionals are still scarce. Thus, the aim of this study was to identify and prioritize health literacy competencies of health professionals in German-speaking countries. Methods A modified, two-round Delphi study was conducted with 24 experts in the field of health literacy or a relevant field from Switzerland, Austria, and Germany. The experts were asked to evaluate and rate different competencies of health professionals regarding health literacy. Results As a result, 14 core competencies have been identified by the experts, including five items referring to the category “knowledge”, seven items to the category “skills” and two items referring to the category “attitude”. The identified competences indicate that health literate health professionals understand health literacy’s importance, employ clear communication techniques, and actively engage patients to ensure comprehension. Furthermore, health literate health professionals recognize cultural barriers, use plain language, and maintain that effective communication is crucial for quality healthcare. Among the 14 core competencies, communication practices were reported to be of particular importance for practice-oriented, professional health literacy skills of health professionals. Conclusions The identified set of health literacy competencies provides an essential groundwork for future assessments of competencies concerning professional health literacy among health professionals, their integration into curricula, and further development of tailor-made trainings and education.